TEO-DEMOKRASI BERBASIS PERTANGGUNGJAWABAN: STUDI KOMPARATIF ATAS RESPONS S.M. ZAFAR DAN MEHDI BAZARGAN TENTANG SISTEM PEMERINTAHAN ISLAM - Toto Suharto (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This article seeks to examine and analyze how the response of two contemporary Islamic thinkers of democracy. Both thinkers are S.M. Zafar and Mehdi Bazargan. They have typical thinking about the system of government. Zafar offers a system of government based on the Theo-democracy parliamentary, because of his opposition to the military system in Pakistan. Whiles Bazargan offers the system of government based on Theo-democracy, because of his opposition to the ‘ulamā’ system of Khomeini’s government. They are looked theo-democracy governance as a system that needs to be implemented in an Islamic state.